1996
DOI: 10.1017/s1357729800028265
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure of cattle walking on a flat terrain

Abstract: A study was carried out to evaluate the effect of horizontal walking upon CO 2 production rate by the carbon dioxide dilution rate technique. This was used as an indicator of animal energy expenditure. Two groups of three 18month-old Aberdeen-Angus steers were assigned to two experiments. Average weights were 290 (s.e. 7-6) kg and 285 (s.e. 1-0) kg for experiments 1 and 2 respectively. Animals were allocated to individual pens and given 5-0 and 4-5 kg dry matter of a mixed diet for experiments 1 and 2 respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It has been calculated that the energy expenditure of grazing animals increases from 17 to 35% depending on the grazing conditions (Osuji 1974; Di Marco et al . 1996; Mendez et al . 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been calculated that the energy expenditure of grazing animals increases from 17 to 35% depending on the grazing conditions (Osuji 1974; Di Marco et al . 1996; Mendez et al . 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The continuous intravenous infusion of a sterile antibiotic solution of ciprofloxacin administered with a human ambulatory pump system simplifies the procedure in unrestrained dairy cows. The ambulatory infusion pump model has a long history of use in human medicine for the home care delivery of antibiotic solutions, and the ambulatory pumps have also been used in animal metabolic studies (Di Marco et al ., ; Mendez et al ., ; Di Marco & Aello, ). The intravenous solution of ciprofloxacin was delivered continuously to the cow to establish a steady鈥恠tate plasma level of this antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported lower estimations of the energetic cost of walking. With the use of the C0 2 entry rate technique, Mendez et al . (1996) estimated the energy requirement of walking for Angus steers that were led by a rope outdoors for 1 or 2 hours at a speed of 3 km/h.…”
Section: Energy Requirement Of Components Of the Activity Of Grazing Ruminantsmentioning
confidence: 99%
“…Sahlu et al(1988) describe a relationship of HP and C0 2 production as: HP (kcal/kg BW 075 /day) = 13.91 + 4.39 C02 (L/kg BW 0 -75 ) A multichannel pump has been used for continuous injection of NaH 14 C0 3 and sampling of saliva to determine the specific activity of C0 2 (Sanchez and Morris, 1984;Sahlu et al . , 1988;Mendez et al . , 1996).…”
mentioning
confidence: 99%